2004
DOI: 10.1563/1548-1336(2004)30<125:apiaym>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

AICRG, Part I: A 6-Year Multicentered, Multidisciplinary Clinical Study of a New and Innovative Implant Design

Abstract: The following conclusions can be made: (1) the implant design was effective under all clinical conditions; (2) no significant and unexpected complications or risk factors were evident; (3) survival was found to be excellent; and (4) this implant is well suited for use in the restoration of masticatory function and esthetics in patients with missing natural teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
19

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 12 publications
2
23
0
19
Order By: Relevance
“…Same implant systems may also permit micromovements at the abutment-implant connection during clinical function that finally leads to localized inflammation and crestal bone loss. 11,23 Conversely, the subcrestal positioning of implants in the present study resulted in bone located above the implant shoulder, as demonstrated by the radiographic results of the distance from the top of the implant to the first boneto-implant contact at the interimplant region (I-IR). The reason for this finding could not be deduced from the present data, but it has been speculated 13,24-26 that the Morse cone connection that allows abutments to emerge from a more central area of the implant (platform-shifting protocol) may help to protect the peri-implant soft and mineralized tissues FIGURES 4-6.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Same implant systems may also permit micromovements at the abutment-implant connection during clinical function that finally leads to localized inflammation and crestal bone loss. 11,23 Conversely, the subcrestal positioning of implants in the present study resulted in bone located above the implant shoulder, as demonstrated by the radiographic results of the distance from the top of the implant to the first boneto-implant contact at the interimplant region (I-IR). The reason for this finding could not be deduced from the present data, but it has been speculated 13,24-26 that the Morse cone connection that allows abutments to emerge from a more central area of the implant (platform-shifting protocol) may help to protect the peri-implant soft and mineralized tissues FIGURES 4-6.…”
Section: Discussionmentioning
confidence: 59%
“…[8][9][10] Implants with Morse cone connections feature internal, tapered, and conical abutments to eliminate the microgap often found in 2-stage implant systems. The implant/abutment connection of these systems and the microgap may allow repetitive micromovements between the parts during clinical function, 11 as well as accumulation of food debris and bacteria, both of which can lead to localized inflammation and crestal bone loss. [12][13][14] This system uses the platformshifting protocol for restoration, in which the abutment is 1 mm narrower than the implant platform at the time of surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low elastic modulus of trabecular bone acts as a stress breaker that promotes better dissipation of stresses from the occlusal loading. 28 However, the peak stress was substituted by higher implant displacement. In the present study, all models exhibited implant displacement below the threshold of 150 µm required to prevent fibrous tissue formation; 2 these are in the same range reported by a previous study using FEA.…”
Section: Discussionmentioning
confidence: 99%
“…Morris et al [10] in their publication, showed that within a 5-year period, from among 1500 implants, 98.3% of all conical abutment (DENTSPLY Friadent ANKYLOS®) implants survived. What is more, relatively high survival rates (98.2%) were seen involving 275 DENTSPLY Friadent ANKYLOS® implants loaded prosthetically in the form of a single crown, during an 8-year follow-up period [2].…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%